The small intestine as a model for evaluating adult tissue stem cell drug targets - Potten, Christopher S. (Blackwell Publishing Ltd., 2003)

(untitled) (Cell Prolif)
Abstract.  Adult tissue stem cells are defined and some current controversies are discussed. These crucial cells are responsible for all cell production in renewing tissues, and play a vital role in tissue regeneration. Although reliable stem cell markers are generally unavailable for adult epithelial tissues, the small intestinal crypts are an excellent in vivo model system to study stem cells. Within this tissue, the stem cells have a very well‐defined cell position, allowing accurate definition of stem cell specific events. Clonal regeneration assays for the small intestine allow stem cell survival and functional competence to be studied. The ultimate lineage ancestor stem cells are extremely efficiently protected from genetic damage, which accounts for the low cancer incidence in this tissue. Some of the regulatory networks governing stem and transit cell behaviour are beginning to be understood and it is postulated that p53 plays a crucial role in these processes.